Agricultural Households And Farmer Welfare In North Kolaka Regency - Salahuddin; La Ode Muh Munadi; Muhammad Amrullah Pagala; Rina Astarika (International Journal of Science, Technology & Management, 2021)
The research aims to describe the household loss of food crops, farms, and plantations as well as the welfare of farmers' households in North Kolaka Regency in January-March 2021 referring to national indicators or provisions in the processing of agricultural survey results (ST) that have been conducted by national official institutions, namely the Central Statistics Agency (BPS) of Southeast Sulawesi in 2013 (ST2013) and the results of the Inter-Census middle Survey 2018. The results of the analysis of household income and welfare of agricultural households in North Kolaka Regency showed that food crops in the form of rice 39.36, crops 226.71, farms 12.99, plantations -0.31, and farmers welfare level 6.22. Keywords: Household Violence, Farmer Welfare, North Kolaka